Enhancing Repayment Discipline in Islamic Microfinance Through Mosque-Based Social Networks: The Case of Bank Aceh Shariah - Ropeet Jeama; Israk Ahmadsyah (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2026)
Islamic microfinance institutions (IMFIs) face persistent challenges in identifying trustworthy borrowers among low-income communities, often resulting in elevated non-performing financing (NPF) levels. Bank Aceh Shariah, a municipally supported Islamic microfinance entity, seeks to address this issue by leveraging mosque-based social networks to strengthen borrower screening, monitoring, and repayment commitment. This study examines the potential of a cooperative framework between Bank Aceh Shariah and mosque consortia in Banda Aceh to enhance Islamic microfinance sustainability. The concept utilizes moral–religious capital, social cohesion, and community-based trust mechanisms inherent within mosque congregations (jamaah) to incentivize honesty and strengthen repayment discipline. The expected outcome is a reduction in NPF rates through enhanced character-based financing assessment and communal accountability. The paper contributes to the growing discourse on Islamic social finance innovations by demonstrating how religious institutions can support ethical borrowing behavior and financial inclusion in Muslim-majority contexts.